Metabolic Syndrome and Metabolic Dysfunction-associated Steatotic Liver Disease in Fibromyalgia - Chen, Chia-Chang; Chen, Yi-Hsing; Chen, Der-Yuan; Yang, Sheng-Shun; Tang, Kuo-Tung (Archives of Rheumatology, 2025)
Background/Aims: Fibromyalgia (FM) is a chronic disease characterized by widespread pain. An increased cardiovascular risk has been suggested in these patients. The aim was to investigate the cardiovascular risk factors in these patients. Materials and Methods: Patients with primary FM consecutively were prospectively recruited from a tertiary medical center in Taiwan. As the control group, individuals without FM who had undergone a health checkup examination were recruited. Their traditional cardiovascular risk factors, carotid intima-media thickness (IMT), and the presence of metabolic syndrome were then determined. Metabolic dysfunction–associated steatotic liver disease (MASLD) and the severity of hepatic steatosis (the Saverymuttu and Hamaguchi scores) were both determined by sonography. Multivariate logistic and linear regression were used to compare groups of subjects. Results: A total of 66 FM patients and 116 controls were recruited. Between FM patients and controls, comparable cardiovascular risk factors were found, including carotid IMT and metabolic syndrome. FM patients had a higher proportion of central adiposity when compared with the controls, with an odds ratio of 6.1 (95% CI: 2.9, 13.1). Fibromyalgia patients had a more severe hepatic steatosis, if present, as determined by the Hamaguchi score. In female subjects, FM patients had a higher proportion of MASLD when compared with the controls, with an odds ratio of 2.8 (95% CI: 1.3, 6.1). The disease severity was associated with left IMT value and lipid blood levels in FM patients. Conclusion: Fibromyalgia patients had a higher proportion of central adiposity and more severe hepatic steatosis when compared with the controls. Those patients with more severe FM symptoms likely had a higher cardiovascular risk. Metabolic dysfunction–associated steatotic liver disease merits more attention in FM patients. Cite this article as: Chen C, Chen Y, Chen D, Yang S, Tang K. Metabolic syndrome and metabolic dysfunction-associated steatotic liver disease in fibromyalgia. Arch Rheumatol. 2025;40(4):452-458.